Soviet foreign policy and the revolutions of 1989 in Eastern Europe - Asmus, Ronald D.; Brown, J. F. (James F.), 1928-2009; Crane, Keith, 1953-; Rand eBooks (Santa Monica, CA : RAND, 1991)
This report analyzes the collapse of Communist rule in Eastern Europe in 1989 and assesses the role of changes in Soviet foreign policy in precipitating this collapse. It finds that the preceding 40 years of economic and social failure by the Communist regimes, the illegitimacy of Communist rule, the consolidation of societal opposition, loss of confidence in the ruling elites, and the improvement in East-West relations created the conditions leading to the collapse of Communist rule. However, the change in Soviet foreign policy under Gorbachev was the precipitating event. Once change began, the removal of the Communist leadership in one country led to upheavals in others. The Soviet leadership did not foresee the collapse of Communism in Eastern Europe; rather, it believed that the old regimes would be replaced by reformers. It also failed to see the unification of Germany as an outcome of the collapse of the Honecker regime. In the future, Soviet influence in Eastern Europe will be diminished but will not ebb to the low levels of the pre-World War II era. Economic and mutual security concerns will continue to tie Eastern Europe to the Soviet Union (or its successor), although much more loosely than in the past.
"National Defense Research Institute"--Cover.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Europe, Eastern -- Foreign relations -- Soviet Union; Europe, Eastern -- Politics and government -- 1945-1989.; Soviet Union -- Foreign relations -- 1985-1991.; Soviet Union -- Foreign relations -- Europe, Eastern; Electronic books